2015
DOI: 10.1016/j.ultsonch.2015.01.018
|View full text |Cite
|
Sign up to set email alerts
|

N-Sulfonylation of amines, imides, amides and anilides using p-TsCl in presence of atomized sodium in EtOH–THF under sonic condition

Abstract: a b s t r a c tA simple, facile and an efficient procedure for the N-sulfonylation of amines, imides, amides and anilides using p-TsCl in the presence of atomized sodium in a mixture of EtOH-THF under sonic condition is developed. The method is rapid, mild and inexpensive; yields are high and the reactions go to completion within 2-8 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…From these studies emerged the important role played by acylsulfonamide moiety: It represents not only a bioisosteric replacement of carboxylic acid, but also it establishes good interactions within EP 3 receptor. Several new EP 4 antagonists show acylsulfonamide structure: GW-627368X (22) and BGC-20-1531 (23) are benzenesulfonamide derivatives with high EP 4 affinity. It is also implicated in pathological conditions, such as cancer growth and metastasis, and in some inflammatory diseases.…”
Section: Ep 3 -Ep 4 Receptor Antagonists (Prostanoid Receptor Antagmentioning
confidence: 99%
“…From these studies emerged the important role played by acylsulfonamide moiety: It represents not only a bioisosteric replacement of carboxylic acid, but also it establishes good interactions within EP 3 receptor. Several new EP 4 antagonists show acylsulfonamide structure: GW-627368X (22) and BGC-20-1531 (23) are benzenesulfonamide derivatives with high EP 4 affinity. It is also implicated in pathological conditions, such as cancer growth and metastasis, and in some inflammatory diseases.…”
Section: Ep 3 -Ep 4 Receptor Antagonists (Prostanoid Receptor Antagmentioning
confidence: 99%
“…The sufonylation of heteroarylamines was reported by several methods . Recently, we have reported N ‐sulfonylation reaction in the presence of dispersed sodium where in the reaction proceeded at a faster rate with high yields . In fact, the reaction of 1 with methyl 2‐(chlorosulfonyl)acetate ( 4 ) in the presence of dispersed sodium under ultrasonication gave methyl 2‐( N ‐(4‐(4‐thiophen‐2‐yl)oxazol‐2‐yl)sulfamoyl)acetate ( 5 ) in excellent yield.…”
Section: Resultsmentioning
confidence: 99%
“…The same reaction under ultrasonic irradiation proceeded at a faster rate but there is no improvement in the yield of the product ( Table ). The literature survey indicated that N ‐sulfonylation of imidazoles and benzimidazoles is accomplished in the presence of sodium in polar solvents under ultrasonication . Moreover, a variety of organic reactions are performed to get the desired molecules by employing sodium in polar solvents under sonication .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the use of fine dispersed sodium (atomized sodium) attains importance since the reaction proceeds at a faster rate in the presence of dispersed sodium . Hence, the reaction between 1a and 2 is performed in the presence of dispersed sodium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation